Pengaruh Lokasi, Biaya Pendidikan, dan Word of Mouth Terhadap Keputusan Memilih Pondok Pesantren (Studi Kasus Pada Pondok Pesantren Shirotul Fuqoha Putri) - Syairotun Nadzifah; Muhammad Ridwan Basalamah; Tri Sugiarti Ramadhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted to determine the location, cost of education, and word of mouth on the decision to choose an Islamic boarding school. The case study was at the Shirotul Fuqoha Putri Islamic boarding school which is located at Jalan Basuki Rahmat No.104, Dusun Krajan, Sepanjang, Kec. Gondanglegi, Malang Regency. The method used is quantitative which aims to explain the position of each variable and its influence between one variable and another variable, and the data source used is primary data, namely by distributing questionnaires with Linkert class to the guardians of the students of the Islamic boarding school Shirotul Fuqoha Putri. The sample calculation in this study used the slovin formula which produced 86 respondents. The results of this study are the variables of location, cost of education, and word of mouth simultaneously influence the decision to choose a boarding school. Partially, the cost of education and word of mouth have an effect on the decision to choose a boarding school, while the location has no effect on the decision to choose a boarding school. Keywords: Location, Cost Of Education, Word of Mouth, and Decision to Choose